Larval description of Setodes acutus Navás 1936, (Trichoptera: Leptoceridae) from Algeria, including a discriminatory matrix to the known Setodes larvae from the Maghreb region - Dambri, Besma M; Bemmoussat-Dekkak, Soumya; Ibrahimi, Halil; Sartori, Michel; Karaouzas, Ioannis (Zootaxa, 2024)
The hitherto unknown larva of Setodes acutus Navás 1936 from the Aures region, Algeria, is described. The diagnostic features of the species are explained and illustrated, and morphological comparisons are made with Setodes argentipunctellus McLachlan 1877, recently recorded from the region. In addition, a discriminatory matrix to the known Setodes larvae from the Maghreb region is provided. Lastly, information on the ecology of the two species and their distribution to Northwest and Northeast Algeria is included.